PENERAPAN MODEL SIKLUS BELAJAR ( LEARNING CYCLE 5E) DENGAN CATATAN TERBIMBING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKA SISWA DI SMPN 11 JEMBER KELAS VIIB TAHUN AJARAN 2011/2012 - Mustangin - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
Physics  is  an  adaptive  lesson  that  gives  students  basic  knowledge  of natural law. Some of students in junior high school and senior high school think that physics is not fun lessons because the process of physics learning in school the theacher  just  give  formula  to  remember  not  the  right  physics  concept. Learning about physics should give direct experince to develop science knowledge and understand surrounding natural scientifically. One of the physics learning activities supposed to meet that is learning cycle 5E with guide note. Learning cycle 5E with guide note focused on improving students’ motivation . After administering this learning cycle 5E with guide note method,  the result  is  (1)  improving  students’  activity (2)  improving  students’ achievement of the VII B grade of State Junior High School 11 Jember at the 2011/2012 academic year. Key words: Learning cycle, Guide Note